IMPLEMENTATION OF ACCOUNTABILITY AND TRANSPARENCY IN FINANCIAL MANAGEMENT OF MIFTAHUL JANNAH MOSQUE IN BLITAR DISTRICT BASED ON ISAK 35 - Kirani Salsabila 123; Ruly Priantilianingtiasari (BALANCE: JOURNAL OF ISLAMIC ACCOUNTING, 2023)
The mosque is a non-profit organization whose accounting records have been regulated by the Interpretation of Financial Accounting Standards No. 35. The problem that has been occurring in society is a lack of knowledge regarding the importance of accountability and transparency in financial management and mosque financial records that have not complied with applicable accounting standards. The purpose of this study was to determine the application of accountability and transparency in financial management at the Great Miftahul Jannah Mosque in Blitar Regency and to analyze the financial reports at the Miftahul Jannah Grand Mosque in Blitar Regency, whether they are in accordance with ISAK 35. The method used is a qualitative case study. The results of this study indicate that accountability and transparency in the financial management of the Miftahul Jannah Grand Mosque as a whole have been implemented and are running well. The Miftahul Jannah Grand Mosque has not presented financial reports in accordance with ISAK 35, only presents financial reports in the form of cash in and cash out only in the General Cash Book and Financial Accountability Report.